2019
DOI: 10.22159/ajpcr.2019.v12i9.34464
|View full text |Cite
|
Sign up to set email alerts
|

Cussonia Spicata Thunb. In Tropical Africa: Phytochemistry, Pharmacology, and Medicinal Potential

Abstract: Cussonia spicata is an evergreen tree widely used as herbal medicine throughout its distributional range in tropical Africa. The current study is aimed at providing a critical review of the phytochemistry, pharmacology, and evaluation of the medicinal potential of C. spicata. Documented information on the phytochemistry, pharmacology, and medicinal applications of C. spicata was collected from several online sources which included BMC, Scopus, SciFinder, Google Scholar, Science Direct, Elsevier, PubMed, and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Abdominal pain Bark and root decoction are taken orally South Africa [5,53] Antifebrile and fever Leaf, root bark, and root decoction are taken orally South Africa [5,17,[53][54][55][56][57] Appetite stimulant Root decoction is taken orally South Africa [5,41] Cardiovascular Not specified Zimbabwe [5,16] Convulsions and epilepsy Leaf infusion sprinkled on the face and taken orally Zimbabwe [5,16,35,39] Diabetes mellitus Root decoction is taken orally South Africa [5,58] Diuretic A root infusion is taken orally South Africa [5,17,55,59,60] Emetic, nausea, and vomiting Fruit, root, and stem infusion taken orally Eswatini and South Africa [2,5,14,17,[53][54][55][56][57]61] (Table 1). Continued.…”
Section: Spicatamentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal pain Bark and root decoction are taken orally South Africa [5,53] Antifebrile and fever Leaf, root bark, and root decoction are taken orally South Africa [5,17,[53][54][55][56][57] Appetite stimulant Root decoction is taken orally South Africa [5,41] Cardiovascular Not specified Zimbabwe [5,16] Convulsions and epilepsy Leaf infusion sprinkled on the face and taken orally Zimbabwe [5,16,35,39] Diabetes mellitus Root decoction is taken orally South Africa [5,58] Diuretic A root infusion is taken orally South Africa [5,17,55,59,60] Emetic, nausea, and vomiting Fruit, root, and stem infusion taken orally Eswatini and South Africa [2,5,14,17,[53][54][55][56][57]61] (Table 1). Continued.…”
Section: Spicatamentioning
confidence: 99%
“…The family Araliaceae is reported to have 55 genera and over 1500 species and infraspecific taxa [1] distributed in tropical, subtropical, and temperate regions. The members of the family Araliaceae are known to have various classes of secondary metabolites, which are characterized by several phytochemical properties [2][3][4][5][6][7][8][9]. Research by Kinghorn and Balandrin [10] showed that natural products and their phytochemical compounds represent more than 50% of all pharmaceutical drugs in clinical use worldwide.…”
Section: Introductionmentioning
confidence: 99%